2014
DOI: 10.1007/s00330-014-3489-y
|View full text |Cite
|
Sign up to set email alerts
|

First metatarsophalangeal joint- MRI findings in asymptomatic volunteers

Abstract: • Cartilage defects of asymptomatic first metatarsophalangeal joints were common on MRI. • The collateral ligaments were often heterogeneous in structure and showed increased signal intensity. • Areas of increased signal intensity within the flexor and extensor tendons were rare. • These observations need to be considered in MR examinations of symptomatic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Specifically, subtle injuries of the soft-tissue stabilizers, for example, or leakage of contrast from a ruptured plantar plate could go undetected on X-ray, computed tomography (CT), and arthrography. 19,28,36,37…”
Section: Imagingmentioning
confidence: 99%
“…Specifically, subtle injuries of the soft-tissue stabilizers, for example, or leakage of contrast from a ruptured plantar plate could go undetected on X-ray, computed tomography (CT), and arthrography. 19,28,36,37…”
Section: Imagingmentioning
confidence: 99%
“…Previous reports [ 19 , 20 ] showed that the plantar plate of the first MTPJ differed from that of the lesser ones (2–5) in that it spanned between the proximal phalangeal base and metatarsal head with the intervening hallux sesamoids. There are discrepancies when describing the components of the plantar plate [ 11 , 13 , 16 , 21 25 ]. Some studies [ 2 , 15 ] reported that the plantar plate arose from the distal margin of the intersesamoid ligament and extended distally toward the base of the proximal phalanx.…”
Section: Discussionmentioning
confidence: 99%
“…Two musculoskeletal radiologists measured the capsuloligamentous complex of the first MTPJ of the MR images independently. All measurements were taken three times in the middle of their respective courses of the optimal MRI images plane [ 1 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) can be useful in ambiguous cases; however, it needs to be interpreted with caution as they have been shown to overestimate the degree of injury. Dietrich et al obtained MRIs in 30 asymptomatic volunteers and found that the collateral ligaments frequently contained hyperintense areas on fluid-weighted sequences with fat suppression and on intermediate weighted sequences [12].…”
Section: Workupmentioning
confidence: 99%